2003
DOI: 10.1074/jbc.m302232200
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Organ Vascularization and Lipoplex-Serum Initial Contact in Intravenous Murine Lipofection

Abstract: Following intravenous administration of cationic lipid-DNA complexes (lipoplexes) into mice, transfection (lipofection) occurs predominantly in the lungs. This was attributed to high entrapment of lipoplexes in the extended lung vascular tree. To determine whether lipofection in other organs could be enhanced by increasing the degree of vascularization, we used a transgenic mouse model with tissue-specific angiogenesis in liver. Tail vein injection of N-(1-(2,3-dioleoyloxy)propyl)-N,N,N-trimethylammonium chlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
102
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(110 citation statements)
references
References 42 publications
6
102
2
Order By: Relevance
“…However, this is not the explanation here, given that in our nanoparticles, no aggregation or increased sized was observed in the presence of serum. Other authors stated that the bigger particle size in the presence of serum decreased transfection [34,35]. The lower zeta potential due to the binding to anionic serum proteins can also contribute to this enhancement [36][37][38], but here, the charge was positive enough that the particles were not converted to negatively charged particles in the presence of serum, and the systems became serum-resistant.…”
Section: Discussionmentioning
confidence: 98%
“…However, this is not the explanation here, given that in our nanoparticles, no aggregation or increased sized was observed in the presence of serum. Other authors stated that the bigger particle size in the presence of serum decreased transfection [34,35]. The lower zeta potential due to the binding to anionic serum proteins can also contribute to this enhancement [36][37][38], but here, the charge was positive enough that the particles were not converted to negatively charged particles in the presence of serum, and the systems became serum-resistant.…”
Section: Discussionmentioning
confidence: 98%
“…The lyophilized 'cake' was hydrated with 20 mM Hepes, pH 7.4, and vortexed for several minutes to form UHV, mostly uni-and oligolamellar vesicles of B 500 nm. 35 Plasmids pEGFP-C1 plasmid under the control of the CMV promoter, pLNCluc plasmid containing the firefly luciferase gene, pLacZ under the control of the SV40 or CMV promoter, and pCMVhGH were used for quantitative and qualitative assays. Plasmids were purified using the Nucleobond AX 500 column (Machery-Nagel, Duren, Germany) or using the Qiagen Plasmid Mega kit (Hilden, Germany).…”
Section: Liposome Preparationmentioning
confidence: 99%
“…Cholesterol initially used as a helper lipid form more stable but less efficient complexes than those containing DOPE in vitro. However, cholesterol containing lipoplexes have shown a higher rate of biological activity when compared to lipoplexes with DOPE, when these complexes were utilized in vivo Sternberg et al, 1998;Smith et al, 1998;Simberg et al, 2003). The significant transfection activity attained was attributed to an improved cell binding and uptake of the lipoplexes promoted by the presence of cholesterol (Crook et al, 1998) and/or better stability of the lipoplex in serum (Simberg et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, cholesterol containing lipoplexes have shown a higher rate of biological activity when compared to lipoplexes with DOPE, when these complexes were utilized in vivo Sternberg et al, 1998;Smith et al, 1998;Simberg et al, 2003). The significant transfection activity attained was attributed to an improved cell binding and uptake of the lipoplexes promoted by the presence of cholesterol (Crook et al, 1998) and/or better stability of the lipoplex in serum (Simberg et al, 2003). In 1991, Gao et al reported the synthesis and application of the cholesterol-based cationic lipid 3-β-[N-(N′,N′-dimethylaminoethyl)carbamoyl]-cholesterol (DC-Chol, 1a), which was combined with DOPE to transfect mammalian cells (Gao & Huang, 1991 (Zhdanov et al, 1998;Gao & Hui, 2001;Geall et al, 2000;Percot et al, 2004;Ding et al, 2008;Medvedeva et al, 2009;Maslov et al, 2010).…”
Section: Introductionmentioning
confidence: 99%